Volatility Spillover Effects from The US and Japan to the ASEAN-5 Markets and Among the ASEAN-5 Markets - Intan Purbasari (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study examines volatility spillover effects from USA and Japanese to the ASEAN-5 equity markets and volatility spillover among the ASEAN-5 equity markets in the period January 1, 2004 through December 31, 2013. The whole time-period is divided into 3 periods as related to the world financial and economic crisis of 2008-2009, namely : pre-crisis, crisis and post-crisis. Bivariate GARCH (1,1) – FULL BEKK model is employed to simultaneously estimate the conditional variance between 7 different indexes. The following are the results of empirical research : The first, volatility spillover has a different nature and magnitude depending on the period of the pre crisis, crisis and post-crisis. Second, there is evidence that in the pre-crisis period, there are no volatility spillover among the ASEAN-5 stock markets, but the different results shown in the crisis and post-crisis period, during this period of volatility spillover occurs between the ASEAN-5 markets, but in times of crisis the magnitude is larger than the post-crisis. Internal volatility spillover occurs among ASEAN-5 is one-way (unidirectional). Philippine capital market is resistant to the crisis and easily affected by Indonesia, Thailand and Singapore stock market. While in the post-crisis, Indonesian stock market is easily affected by the stock market turmoil that occurred in Singapore and Thailand stock market. Third, there is evidence of volatility spillover from the U.S. and Japan to the ASEAN-5 markets. At the time of pre-crisis period, the Japanese market volatility spillover effect is greater than the American market. While in times of crisis and post-crisis, the U.S. market gives greater influence than the Japanese market. Four, the external relationship between U.S, Japan and the ASEAN-5 markets become more complex during the post-crisis. Five, the countries that have large spillover volatility is influenced by trade and FDI in the form of shares. The tendency is, the higher the trade relations and investor funds were invested in these countries the higher the dependence of the country with partner countries.